Enhancing the curing efficiency and physicochemical properties of acrylated epoxidized palm oil polyurethane coatings via double acrylation-thiol modification - Siti Noor Hidayah, Mustapha; Mohamad Ismail, Mohamad Isa; Muhammad Safwan, Shamsuddin; Rasidi, Roslan; Rohani, Mustapha; Mohd Jumain, Jalil (Springer, 2025)
The slow curing and suboptimal properties of epoxidized palm oil polyurethane acrylate (EPOUA) coatings remain significant challenges that limit their performance. This study enhances these coatings by applying acrylation-thiol (AT) modification onto the EPOUA coatings provided double acrylation-thiol effect to the EPOUA. EPOUA and AT were first synthesized separately, then the AT was blended at concentrations of 2, 4, 6, and 8 parts per hundred resin (phr) EPOUA. The blended mixture was then cast onto a silicone mold with a thickness of 1 mm and cured using ultraviolet (UV) radiation. The results show that 2 and 4 phr AT significantly improved curing, reducing time by 15 and 30 s, respectively. Crosslinking density also increased, with gel content rising by 6% and 9% at 2 and 4 phr AT, respectively, while maintaining low volatile organic compound (VOC) emissions (< 5%). Physical properties improved, with hardness increasing threefold at 2 phr AT and fourfold at 4 phr AT on glass, plywood, and steel. Adhesion remained excellent (5B rating) on plywood, steel, and aluminum. However, higher AT concentrations (6 and 8 phr) resulted in inconsistent curing and increased VOC emissions. These findings indicate that 4 phr AT optimally improves EPOUA coatings’ curing efficiency, crosslinking, and mechanical properties while maintaining environmental compliance.